Analytical model for the load-slip relationship of bearing-shear connectors - Qin, Fengjiang; Huang, Zhipeng; Zheng, Zhichao; Chou, Yaling; Zou, Yang; Di, Jin (Frontiers in Materials, 2023)
The shear behavior of shear connectors in steel-concrete composite structures, mainly depends on its load-slip relationship. The load-slip relationship not only reflects the shear capacity and slip capacity of the shear connectors, but also the degradation of shear stiffness during loading. In this study, fifteen push-out tests were carried out to investigate the load-slip relationship of the novel bearing-shear (B-S) connectors, which consist of pressuring-bearing plates and shear plates. Based on push-out tests, the influence of the shape and height of the pressure-bearing plate, and the shear plate shape on the load-slip relationship of the B-S connectors was analyzed. Then, an effective finite element model, validated by push-out tests, was used to study the influence of the concrete strength, and the thickness and tensile strength of the shear plate on the load-slip relationship of B-S connectors. Finally, based on the push-out tests, numerical analysis and theoretical analysis, an analytical model expressing the load-slip relationship of the B-S connectors was proposed.